Diffusion-Weighted Imaging with Two Different b-Values in Detection of Solid Focal Liver Lesions. (25th February 2016) - Yang, Da-wei; Wang, Ke-yang; Yao, Xun; Ye, Hui-yi; Jiang, Tao; Liu, Yuan; Gao, Jia-yin; Chen, Min; Zhou, Cheng; Yang, Zheng-han
Abstract : One hundred and eighty-two consecutive patients with suspected liver disease were recruited to receive diffusion-weighted imaging (DWI) with two different b -values, in comparison with T2-weighted imaging (T2WI). The detection rate of three MR sequences in solid focal liver lesions (FLLs) and subgroup analyses were performed. Our prospective study found that DWI600 was equivalent to DWI100 and T2WI for the detection of solid FLLs overall but was significantly more accurate in the detection of malignant solid FLLs and lesions larger than 10 mm.